The Pattern of Rebellion in the Poetry of Ibn al-Hajjaj al-Baghdadi (d. 391 AH): Occasional Poetry as a Model - Yasser, Dr. Shaimaa Jouda (Thi Qar Arts Journal, 2023)
This research attempts to study the pattern of rebellion in occasion poetry by Ibn al-Hajjaj al-Baghdadi. There are patterns that the poet attempted to convey through his poetry. The poet rebelled against everything that contradicted norms and exceeded all boundaries, using language that bordered on absurdity and satire. In fact, through this rebellious breach, he challenged authority and the significant transformations that the Islamic society underwent, considering it an external exploiter. With this rebellious movement, he aimed to reject reality and stood alone in working across political, social, and religious domains in which he lived. Essentially, his rebellion constituted a continuous confrontation against the aspects of decay in politics, religion, and society as a whole, targeting both the ruling authority and the masses, as they represent the hierarchical structure of power in all its manifestations. However, the elements of Arab authenticity in the revolutionary nature fuel the values for countering this reality and critiquing it poetically.